The story of "me" : contemporary American autofiction - Worthington, Marjorie (University of Nebraska Press, 2018)
"The Story of "Me" shows that the burgeoning of autofiction serves as a barometer of American literature from modernist authorial effacement to postmodern literary self-consciousness"-- Provided by publisher
Keywords: Autobiographical fiction -- History and criticism.; American fiction -- 20th century -- History and criticism.; American fiction -- 21st century -- History and criticism.; Autobiography in literature.; Self in literature.; Postmodernism (Literature) -- United States.; Roman américain -- 20e siècle -- Histoire et critique.; Roman américain -- 21e siècle -- Histoire et critique.; Autobiographie dans la littérature.; Moi (Psychologie) dans la littérature.; Postmodernisme (Littérature) -- États-Unis.; LITERARY CRITICISM -- American -- General.; American fiction; Autobiographical fiction; Autobiography in literature; Postmodernism (Literature); Self in literature; United States; Autobiografische Literatur; Autobiografischer Roman; Selbstdarstellung -- Motiv; USA; 1900-2099; Electronic books.; Criticism, interpretation, etc.